2018
DOI: 10.1001/jamaneurol.2018.0963
|View full text |Cite|
|
Sign up to set email alerts
|

Chemotherapy-Induced Peripheral Neuropathy in Long-term Survivors of Childhood Cancer

Abstract: In light of the excellent long-term survival of childhood cancer patients, it is imperative to screen for factors affecting health, function, and quality of life in long-term survivors. OBJECTIVE To comprehensively assess chemotherapy-induced peripheral neuropathy in childhood cancer survivors to define disease burden and functional effect and to inform screening recommendations. DESIGN, SETTING, AND PARTICIPANTS In this cross-sectional observational study, cancer survivors who were treated with chemotherapy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 65 publications
0
44
0
3
Order By: Relevance
“…Neuropathic descriptors such as burning, and shooting are often used, along with numbness and paraesthesia, although pain is not always a presenting feature [42]. CIPN can persist for many years, with a detailed assessment of long term survivors of childhood cancers finding ~48% of individuals having some evidence of neuropathy: predominantly sensory dysfunction and reduced quality of life [51] Some of the clinical features of CIPN are shown in figure 1.…”
Section: The Clinical Syndromementioning
confidence: 99%
“…Neuropathic descriptors such as burning, and shooting are often used, along with numbness and paraesthesia, although pain is not always a presenting feature [42]. CIPN can persist for many years, with a detailed assessment of long term survivors of childhood cancers finding ~48% of individuals having some evidence of neuropathy: predominantly sensory dysfunction and reduced quality of life [51] Some of the clinical features of CIPN are shown in figure 1.…”
Section: The Clinical Syndromementioning
confidence: 99%
“…Severe CIPN results in dose reductions and treatment terminations, potentially affecting survival. 2 , 4 , 5 Neuropathy can be long lasting and may worsen after treatment, 6 , 7 leading to disability or an impact on activities of daily living that diminish quality of life. 8 , 9 In order to reduce the incidence of long-term CIPN, 10 , 11 there is a need to identify individual risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different neurophysiological assessment and reporting methods exclude the possibility of making direct comparisons and drawing definitive conclusions. In the largest study to date, published by Kandula et al ( 11 ), a dominant role of sensory neuropathy was found in 50.5% of participants. The time from the completion of cancer treatment was similar to our study (1.5–29 years).…”
Section: Discussionmentioning
confidence: 94%